2010
DOI: 10.1111/j.1464-5491.2009.02896.x
|View full text |Cite
|
Sign up to set email alerts
|

Does diabetes‐related distress explain the presence of depressive symptoms and/or poor self‐care in individuals with Type 1 diabetes?

Abstract: Aims To examine the relationship between depressive symptomatology, diabetes-related distress and aspects of diabetes self-care in a cohort of individuals with Type 1 diabetes. Methods Individuals with Type 1 diabetes taking part in the Pittsburgh Epidemiology of Diabetes Complications Study completed the Beck Depression Inventory (BDI), the Center for Epidemiologic Studies Depression (CES-D) Scale and the Problem Areas in Diabetes (PAID) scale. Self-care was measured by physical activity in the past week an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 22 publications
7
54
1
Order By: Relevance
“…Diabetes distress was positively related to A1C. This finding is congruent with previous studies [12] and highlights the serious psychological burden of managing this complex chronic disease and the effect that burden may have on behaviors. However, FOH was not significantly related to diabetes distress, eating styles, or A1C.…”
Section: Discussionsupporting
confidence: 90%
“…Diabetes distress was positively related to A1C. This finding is congruent with previous studies [12] and highlights the serious psychological burden of managing this complex chronic disease and the effect that burden may have on behaviors. However, FOH was not significantly related to diabetes distress, eating styles, or A1C.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies suggest DD is not associated with self-monitoring of blood glucose, smoking and alcohol consumption, and that its association with physical activity may be explained by more general emotional distress (13).This evidence base is very much underdeveloped at present, though. Martyn-Nemeth (2014) identified that there may be a level at which DD becomes immobilising resulting in fewer behaviours to avoid hypoglycaemia at very high levels of DD (6).…”
Section: Self-management Behavioursmentioning
confidence: 87%
“…For example, studies have demonstrated close relationships between diabetic peripheral neuropathy severity, neuropathy symptoms, and functional impairment on the one hand and symptoms of depression on the other, both cross-sectionally and longitudinally [27, 28]. Moreover, diabetes complications have been cross-sectionally associated with increased diabetes distress [25, 29, 30] and predict the onset of significant diabetes distress over time, with the occurrence of negative life events amplifying the strength of this relationship [25]. Type 2 diabetes patients prescribed insulin, who often have greater diabetes severity and more demanding self-management requirements, also report increased diabetes distress as compared to patients on oral medications only or those not prescribed medication [13, 31].…”
Section: Introductionmentioning
confidence: 99%